x2-3x-4=0 Two solutions were found : x = 4 x = -1 Step by step solution : Step 1 :Trying lớn factor by splitting the middle term 1.1 Factoring x2-3x-4 The first term is, x2 its ...

Bạn đang xem: Attention required!

x^3 + 3x - 4 = 0 factor x^3 + 3x -4 using polynomial division: x^3 + 3x - 4 step 1: find all factors of the constant term, 4. 1, 2, 4 Try each factor above using the remainder Theorem Substitute ...
x3-2x-4=0 Three solutions were found : x = 2 x =(-2-√-4)/2=-1-i= -1.0000-1.0000i x =(-2+√-4)/2=-1+i= -1.0000+1.0000i Step by step solution : Step 1 :Polynomial Roots Calculator : 1.1 ...
Using the formula cos(3x) = 4cos^3(x) - 3cos(x) is actually quite useful, but first we have to vị x=2y , then we get 8y^3 - 6x + 1 = 0 Now we have the 4:-3 ratio và we can sub in y=cos( heta) ...

Xem thêm: Người Mẫu Khả Trang Tiết Lộ Bị Bạo Hành Đến "Thân Tàn Ma Dại

displaystylex^3-3x-2=left(left(x+1 ight)left(x+1 ight)left(x-2 ight) ight) Explanation:Given: displaystyleleft( extXXX ight)left(1 ight)x^3-left(3 ight)x-left(2 ight) ...
More Items

left< eginarray l l 2 và 3 \ 5 & 4 endarray ight> left< eginarray l l l 2 & 0 & 3 \ -1 & 1 & 5 endarray ight>

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు